Keynes and Wall Street. Issue 2 (25th July 2016) - Chambers, David; Kabiri, Ali
Abstract : This article examines in detail how John Maynard Keynes approached investing in the U.S. stock market on behalf of his Cambridge College after the 1929 Wall Street Crash. We exploit the considerable archival material documenting his portfolio holdings, his correspondence with investment advisors, and his two visits to the United States in the 1930s. While he displayed an enthusiasm for investing in common stocks, he was equally attracted to preferred stocks. His U.S. stock picks reflected his detailed analysis of company fundamentals and a pronounced value approach. Already in this period, therefore, it is possible to see the origins of some of the investment techniques adopted by professional investors in the latter half of the twentieth century.